A relação entre ser humano e natureza na modernidade observada pelo espelho do direito - Rosa, Michel Fernandes da (2013)
This paper seeks to identify some reflexes of the modernity as a scientific and social paradigm in the way by which the relationship between human being and nature is regulated by law. Therefore, we will approach the issue of the formation of paradigm of modernity and its influence on the law as a science that sought to adapt itself to this model. Having done this, we intend to demonstrate how the law was used to implement the ideals of modernity and how this was reflected in the regulating of the relationship with nature through the right of property.